EARTHQUAKE RESISTANCE OF TIMBER STRUCRUTRES - Panayotov, Panayot; Petkova, Silvana (Innovation in Woodworking Industry and Engineering design, 2013)
The prime objective of this paper is to describe the basics of the seismic design of the timber constructions. The experience from North America and Japan shows that when designed properly wooden structures can resist extreme conditions like earthquakes. The ability of structures to develop plastic deformations without drastic reduction of strength and resistance is called ductility. The purpose of this paper is to present the ductile behavior of the timber structures in tree directions – material; element/joints; structure as a whole. Timber has orthotropic properties and although it behaves in ductile manner when loaded under compression, especially perpendicular to the grain, it is brittle under tension perpendicular to the grain. The connections in timber structures introduce a foundational aspect in terms of the seismic behavior of the construction, since they act as ductile valves and enable dissipation of energy. Due to its global ductility, the structure posses the ability to withstand deformations without developing high stress concentrations. Seismic resistance of timber structures is based on their advantages – a low-self load; ductile joints; in general very regular building layouts. The paper was done as a specialized literature survey and is based on the conceptions of the capacity seismic design and the system of structural Eurocode standards (EN 1995-1-2:2004 and EN 1998-1:2004).